Managing a Colonoscopic Perforation in a Patient with No Abdominal Wall - Jayan George; Michael Peirson; Samuel Birks; Paul Skinner (Case Reports in Surgery)
We describe the case of a 37-year-old gentleman with Crohn’s disease and a complex surgical history including a giant incisional hernia with no abdominal wall. He presented on a Sunday to the general surgical on-call with a four-day history of generalised abdominal pain, nausea, and decreased stoma output following colonoscopy. After CT imaging, he was diagnosed with a large colonic perforation. Initially, he was worked up for theatre but following early senior input, a conservative approach with antibiotics was adopted. The patient improved significantly and is currently awaiting plastic surgery input for the management of his abdominal wall defect.